Sustentabilidade de agroecossistemas de mandioca: primeiro ciclo de avaliação em Bom Jesus-RN - Silva, Valdenildo Pedro da; Cândido, Gesinaldo Ataide (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2014)
This article presents the sustainability assessment of cassava-producing family agroecosystems in Bom Jesus municipality, Rio Grande do Norte, Brazil, from the perspective of the Framework for Assessing the Sustainability of Natural Resource Management Systems (Mesmis, for its acronym in Spanish). With the measurement of 18 simple strategic indicators of sustainability between cassava-producing agroecosystems, the differences between the sustainability of cassa- va-producing agroecosystems were highlighted, with regard to economic, social and environmental dimensions, comparing the conventional system (which pro- duces cassava in monoculture for trade, using agrochemicals) with the alternative (which performs polyculture preserving natural resources and uses agroecolo- gical techniques). Based on the theoretical and methodological support, it was concluded that the cassava-producing alternative agroecossystem was more sus- tainable than the conventional, for the first presented a desired situation of sus- tainability, resulting from the diversity of agriculture and agroecological principles, whilst the second prioritized raising productivity or economic growth, neglecting sustainability aspects of environmental and social dimensions.